A hybrid approach for heat integration in water conservation networks through non-isothermal mixing. (15th October 2021) - Kamat, Shweta; Bandyopadhyay, Santanu
Abstract: Energy and water resources are conserved simultaneously by optimizing heat integrated water conservation networks using numerical optimization or Pinch Analysis tools. Although numerical optimization provides a general framework, it does not impart physical insights into the problem. In contrast, Pinch Analysis tools enhance the visualization but cannot handle complexities. This paper combines the benefits of Pinch Analysis with numerical optimization to develop an algorithm to minimize the total annualized cost through a hybrid approach. The proposed algorithm comprises two linear programming models, minimizing the water and thermal energy requirement. A novel heuristic is proposed in this paper to incorporate non-isothermal mixing within a linear programming framework. Once the non-isothermal mixing streams are identified, the thermal energy consumption, heat exchanger area, and the number of heat exchanger units are minimized through Pinch Analysis. The proposed algorithm targets water, thermal energy, and heat exchanger requirements ahead of the system's design. The efficacy of the proposed algorithm is illustrated through two examples from the literature. The proposed algorithm provides results that are either superior to (e.g., 18% reduction in total annualized costs) or at par with the numerical optimization techniques, which require models with integer variables and non-linearities to be solved. Graphical abstract: Image 1 Highlights: A hybrid solution strategy is proposed for heat integrated water conservation network. The proposed approach combines linear programming with Pinch Analysis. Heuristic-based linear programming incorporates non-isothermal mixing. The proposed algorithm targets the total annualized cost ahead of the design.